2017
DOI: 10.3389/fmicb.2017.01098
|View full text |Cite
|
Sign up to set email alerts
|

Marine Group II Dominates Planktonic Archaea in Water Column of the Northeastern South China Sea

Abstract: Temperature, nutrients, and salinity are among the important factors constraining the distribution and abundance of microorganisms in the ocean. Marine Group II (MGII) belonging to Euryarchaeota commonly dominates the planktonic archaeal community in shallow water and Marine Group I (MGI, now is called Thaumarchaeota) in deeper water in global oceans. Results of quantitative PCR (qPCR) and 454 sequencing in our study, however, showed the dominance of MGII in planktonic archaea throughout the water column of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 49 publications
9
23
1
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ depth in the tropical North Atlantic Ocean. This is in line with the reported niche preference of MGI archaea for subsurface waters (approximately 50-500 m depth) 10,23,32,34,35 . The MGI archaeal abundance in summer coastal North Sea was 7 × 10 6 cells L −1 , similar to earlier studies 19,28 reporting MGI archaeal abundances of < 1 × 10 7 cells L −1 in summer coastal North Sea SPM.…”
Section: Discussionsupporting
confidence: 90%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ depth in the tropical North Atlantic Ocean. This is in line with the reported niche preference of MGI archaea for subsurface waters (approximately 50-500 m depth) 10,23,32,34,35 . The MGI archaeal abundance in summer coastal North Sea was 7 × 10 6 cells L −1 , similar to earlier studies 19,28 reporting MGI archaeal abundances of < 1 × 10 7 cells L −1 in summer coastal North Sea SPM.…”
Section: Discussionsupporting
confidence: 90%
“…We found even stronger phylogenetic signal in niche differences between abundant MGII OTUs, also suggesting niche partitioning within MGII. MGII as a whole often outcompete MGI within the upper photic zone of temperate/subtropical waters (Liu et al, ; Massana et al, ), which is not the case in this study, as MGII only overwhelmed MGI in YS but at low abundances (Figure ). The patchy distribution of MGII could be reflected by its shallow relationships with measured environmental parameters except DO (Table ).…”
Section: Discussioncontrasting
confidence: 49%
“…Planktonic archaea include four major groups, with Marine Group I (MGI) being currently recognized as marine Thaumarchaeota, and Marine Group II (MGII), Marine Group III (MGIII) and Marine Group IV (MGIV) (L opez-García et al, 2001) being the uncultured groups of Euryarchaeota. While MGII are more abundant in surface waters (Fuhrman and Davis, 1997;Massana et al, 2000;L opez-García et al, 2001;Mincer et al, 2007) and were also found in deep-sea water (Deschamps et al, 2014;Li et al, 2015;Liu et al, 2017), marine Thaumarchaeota are more abundant in meso-and bathypelagic waters (Karner et al, 2001;Herndl et al, 2005;Mincer et al, 2007;Teira et al, 2008;Varela et al, 2008). MGIII are generally considered to be more restricted to deeper waters (Massana et al, 2000;Galand et al, 2009) and, to a lesser extent, the photic zone (Haro-Moreno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%